A critical role of CNT real volume fraction on nanocomposite modulus. (15th April 2022) - Duan, Ke; He, Yonglyu; Liao, Xiangna; Zhang, Jianwei; Li, Li; Li, Xiaobai; Liu, Sihan; Hu, Yujin; Wang, Xuelin; Lu, Yang
Abstract: It is a long-standing puzzle that whether the micromechanical theory is still valid to CNTs-reinforced polymer nanocomposites and why these nanocomposites always show inferior mechanical properties. Herein, we introduced the concept of the real volume fraction for CNT, based on the hypothesis that only the tube walls having direct contact with the polymer matrix carry the external loading. A new micromechanical model on the modulus of nanocomposites was then developed based on this concept. Through a joint study of molecular dynamics (MD) simulations and experimental tests, the correctness and applicability of the proposed micromechanical model were verified, which strongly demonstrate that the micromechanical theory is still applicable to nanocomposites when it sufficiently considers the unique nature of CNTs, such as the real volume fraction, orientations, and aspect ratio. Moreover, the low real volume fraction of multi-walled CNTs is the key reason for the inferior mechanical properties of nanocomposites with uniformly dispersed fillers. Graphical abstract: Image 1 Highlights: Micromechanical theory is still applied to CNTs/epoxy nanocomposites. Low real volume fraction of MWCNTs is the key reason for the inferior nanocomposite stiffness. CNTs in an agglomeration maintain their aspect ratio although the real volume fraction is dramatically reduced.